Increased sensibility to acute acoustic and blast trauma among patients with acoustic neuroma - Marzena Mielczarek; Jurek Olszewski (International Journal of Occupational Medicine and Environmental Health, 2018)
The article shows 2 cases of unusual presentation of acute acoustic trauma and blast injury due to occupational exposure. In the case of both patients the range of impaired frequencies in pure tone audiograms was atypical for this kind of causative factor. Both patients had symmetrical hearing before the accident (which was confirmed by provided results of hearing controls during their employment). A history of noise/blast exposure, the onset of symptoms directly after harmful exposure, symmetrical hearing before the trauma documented with audiograms, directed initial diagnosis towards acoustic/blast trauma, however, of atypical course. Acute acoustic and blast trauma and coexisting acoustic neuroma (AN) contributed to, and mutually modified, the course of sudden hearing loss. In the literature there are some reports pointing to a higher sensitivity to acoustic trauma in the case of patients with AN and, on the other hand, indicating noise as one of the causative factors in AN. Int J Occup Med Environ Health 2018;31(3):361–369